2009
DOI: 10.1371/journal.pone.0005427
|View full text |Cite
|
Sign up to set email alerts
|

CD27− B-Cells Produce Class Switched and Somatically Hyper-Mutated Antibodies during Chronic HIV-1 Infection

Abstract: Class switch recombination and somatic hypermutation occur in mature B-cells in response to antigen stimulation. These processes are crucial for the generation of functional antibodies. During HIV-1 infection, loss of memory B-cells, together with an altered differentiation of naïve B-cells result in production of low quality antibodies, which may be due to impaired immunoglobulin affinity maturation. In the current study, we evaluated the effect of HIV-1 infection on class switch recombination and somatic hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
46
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 45 publications
5
46
1
Order By: Relevance
“…However, in SLE patients, increased frequencies of CD27ϪIgDϪCD95ϩ (17) and CD27ϪIgDϪ memory B cells exhibiting somatic hypermutation of immunoglobulin rearrangements have been found (17,18). Similar populations have been observed in, for example, the tonsil and blood of patients infected with human immunodeficiency virus, as well as in elderly subjects (19)(20)(21)(22), suggesting that an atypical memory B cell population may be generated in response to repetitive activation in secondary lymphoid organs, and that increased numbers of the atypical cells enter the blood of individuals with chronic antigenic stimulation.…”
supporting
confidence: 60%
“…However, in SLE patients, increased frequencies of CD27ϪIgDϪCD95ϩ (17) and CD27ϪIgDϪ memory B cells exhibiting somatic hypermutation of immunoglobulin rearrangements have been found (17,18). Similar populations have been observed in, for example, the tonsil and blood of patients infected with human immunodeficiency virus, as well as in elderly subjects (19)(20)(21)(22), suggesting that an atypical memory B cell population may be generated in response to repetitive activation in secondary lymphoid organs, and that increased numbers of the atypical cells enter the blood of individuals with chronic antigenic stimulation.…”
supporting
confidence: 60%
“…B cell population (Colonna-Romano et al 2009) that has also been shown to be increased in patients affected by SLE, HIV or in healthy subjects challenged with RSV (Cagigi et al, 2009;Fecteau et al, 2006; Table 2 Homing/trafficking receptor phenotype of the four B cell subpopulation in young and elderly donors. Wei et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, in the elderly, we have demonstrated the reduction, in percentage but not in absolute number, of naïve B lymphocytes (IgD (Colonna-Romano et al 2009). DN B cells have also been reported to be expanded in patients affected by SLE, HIV and challenged with RSV (Cagigi et al, 2009;Fecteau et al, 2006;Sanz et al, 2008;Wei et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…This topic is still a somewhat controversial finding, as previously reviewed by us . Moreover, double-negative (DN) B cells (IgD − CD27 − ) are significantly increased in the elderly (Colonna-Romano et al 2009;Bulati et al 2011), as well as under certain pathological conditions, such as systemic lupus erythematosus (SLE) (Anolik et al 2004;Wei et al 2007), chronic HIV infection (Cagigi et al 2009), and in healthy subjects challenged with respiratory syncytial virus (Sanz et al 2008).…”
Section: Cd24mentioning
confidence: 99%
“…This population is also expanded in subjects chronically stimulated (Anolik et al 2004;Wei et al 2007;Sanz et al 2008;Cagigi et al 2009) and might be considered the result of long-enduring stimulation. However, not all subjects or population groups are equally susceptible to the effects of long-term chronic stimulation of the immune system.…”
Section: Cd27mentioning
confidence: 99%